2009
DOI: 10.2217/pgs.09.85
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of the ABCG2 C.421C>A SNP on the Pharmacokinetics of Fluvastatin, Pravastatin and Simvastatin

Abstract: Genetic variability in ABCG2 markedly affects the pharmacokinetics of fluvastatin and simvastatin lactone, but has no significant effect on pravastatin or active simvastatin acid. Genotyping for ABCG2 in addition to SLCO1B1 and ABCB1 polymorphisms could help in predicting statin pharmacokinetics when selecting a statin and its dose for an individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
3
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(134 citation statements)
references
References 35 publications
7
122
3
2
Order By: Relevance
“…Both clinical trials and animal experiments have demonstrated that DM may alter the pharmacokinetic behaviors of some drugs via regulating the expressions and activities of cytochrome P450s (CYP450s) and drug transporters in the liver [16][17][18][19][20][21][22] . Breast cancer resistance protein (Bcrp) and multidrug resistance-associated protein 2 (Mrp2) have also been reported to mediate statin transport [11,23,24] . All of these results suggest that diabetes modifies the disposition of simvastatin as a result of the alterations of these metabolic enzymes and drug transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Both clinical trials and animal experiments have demonstrated that DM may alter the pharmacokinetic behaviors of some drugs via regulating the expressions and activities of cytochrome P450s (CYP450s) and drug transporters in the liver [16][17][18][19][20][21][22] . Breast cancer resistance protein (Bcrp) and multidrug resistance-associated protein 2 (Mrp2) have also been reported to mediate statin transport [11,23,24] . All of these results suggest that diabetes modifies the disposition of simvastatin as a result of the alterations of these metabolic enzymes and drug transporters.…”
Section: Introductionmentioning
confidence: 99%
“…It reduces low density lipoprotein (LDL) cholesterol concentrations by inhibiting cholesterol synthesis in the liver. [14] Many clinical trials have shown that simvastatin reduces the risk of death and other complications in patients with chronic heart disease. [15][16][17] Recently, many studies have reported a relationship between genetic polymorphisms and simvastatin PK.…”
Section: Discussionmentioning
confidence: 99%
“…168 Conversely, the ABCG2 c.421C>A variant, which has been associated with transport activity in vitro, 169 appears to increase the exposure of atorvastatin, fluvastatin, simvastatin lactone, and rosuvastatin by 72%, 72%, 111%, and 144%, respectively, in subjects with the AA genotype compared to those in patients with the wild-type CC genotype. 75,170 Note that this genotype does not appreciably impact the pharmacokinetics of simvastatin acid or pravastatin. 170 As discussed in Absorption above, pravastatin is subject to MRP2-mediated transport in vitro at the level of the enterocyte and hepatocyte.…”
Section: Excretionmentioning
confidence: 99%
“…75,170 Note that this genotype does not appreciably impact the pharmacokinetics of simvastatin acid or pravastatin. 170 As discussed in Absorption above, pravastatin is subject to MRP2-mediated transport in vitro at the level of the enterocyte and hepatocyte. [69][70][71] In vivo, the ABCC2 c.1446C>G variant decreases the exposure of pravastatin (AUC, −68%) compared to wild-type controls secondary to a "gain of function" mutation.…”
Section: Excretionmentioning
confidence: 99%